2019
DOI: 10.5222/terh.2019.08870
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Compliance and Factors Affecting With Isolation Precautions of Nurses: Izmir Sample

Abstract: Hemşirelerin en sık malzeme eksikliğinden dolayı izolasyon önlemlerini uygulamada sıkıntı yaşadıkları saptanmıştır. Sonuç: Hemşirelerin izolasyon önlemleri ile ilgili bilgilerinin hizmet içi eğitimlerle desteklenmesinin ve hastanelerdeki eksik malzemelerin temininin sağlanmasının önemli olduğu düşünülmektedir.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…35 However, Güleç Şatır et al found higher levels of compliance with isolation precautions in women similar to our study. 31 In this study, the total score of the Isolation Precautions Compliance Scale of the nurses working in the operating theatre unit was significantly lower than the nurses working in inpatient unit and intensive care unit. Arli and Bakan also found that the total score of the Isolation Precautions Compliance of the nurses working in the intensive care unit was higher than the nurses working in the clinic.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…35 However, Güleç Şatır et al found higher levels of compliance with isolation precautions in women similar to our study. 31 In this study, the total score of the Isolation Precautions Compliance Scale of the nurses working in the operating theatre unit was significantly lower than the nurses working in inpatient unit and intensive care unit. Arli and Bakan also found that the total score of the Isolation Precautions Compliance of the nurses working in the intensive care unit was higher than the nurses working in the clinic.…”
Section: Discussionmentioning
confidence: 49%
“…30 Considering the total scores of the nurses' Isolation Precautions Compliance Scale in other studies, the scores were determined as 75.52±11.91 in the study of Güleç and 76.55±8.48 in the study of Arli and Bakan, it has been observed that they support our research findings. [31][32][33] In the study of Suliman et al, it was reported that most of the nurses (90%) had good knowladge of isolation measures, but only 65% of nurses had good compliance with isolation precautions. 34 In line with these results, it is thought that compliance with isolation precautions, which are of great importance in controlling the pandemic, is at a good level in nurses.…”
Section: Discussionmentioning
confidence: 99%
“…To determine the number of samples, according to the data of the study by Şatır et al [5], titled “Evaluating the compliance and factors affecting with isolation precautions of nurses: Izmir sample,” using the G*Power 3.1.9.4 software, the minimum number of people to be sampled was found to be 77, predicting an effect size of 0.412 at a 95% confidence level and a 95% power ratio. Two hundred fifteen surgical nurses who accepted to participate in the study and filled out the questionnaire completely were included in the study.…”
Section: Methodsmentioning
confidence: 99%
“…It is known that HAIs, an important health problem in the world and Turkey, are among the most important indicators of quality of care in health institutions [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation